2012
DOI: 10.1177/000313481207800815
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Preoperative Risk Factors for Converting Laparoscopic to Open Cholecystectomy

Abstract: Performing laparoscopic cholecystectomy (LC) always carries the risk of having to convert from laparoscopic to open cholecystectomy (LOC). Being able to identify these patients preoperatively may allow better preoperative planning and lowering operative cost. All LC and LOC were performed by the Eastern Virginia Medical School Department of Surgery retrospectively identified between January 2008 and December 2009. Preoperative risk factors identified in both groups included: age, gender, body mass index greate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
36
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 6 publications
4
36
4
Order By: Relevance
“…3 In a study conducted by Rabindra Nidoni et al in 180 cases found that majority of the patients were in the age group of 31-50years of age. 4 Age>50 years had been found to be a significant risk factor for difficult cholecystectomy by Lee NW et al 5 Kama et al, reviewed 1000 patients of cholelithiasis and found that 41.7% were >60years of age and had conversion rate of 7% as compared to 3.9% in patients <60years of age. 6 The majority of our patients were in the age group of 31-50years of age which corroborate with the study of Prasant S. Dhanke et al and Rabindra Nidoni et al 2,4 In our study it was observed that difficult cholecystectomy was noted in patients 50years of age, which is similar to the study of Lee NW et al and Kama et al 5,6 In a study conducted by Rabindra Nidoni et al in 180 cases found that Male: Female was 1:1.76.…”
Section: Resultsmentioning
confidence: 99%
“…3 In a study conducted by Rabindra Nidoni et al in 180 cases found that majority of the patients were in the age group of 31-50years of age. 4 Age>50 years had been found to be a significant risk factor for difficult cholecystectomy by Lee NW et al 5 Kama et al, reviewed 1000 patients of cholelithiasis and found that 41.7% were >60years of age and had conversion rate of 7% as compared to 3.9% in patients <60years of age. 6 The majority of our patients were in the age group of 31-50years of age which corroborate with the study of Prasant S. Dhanke et al and Rabindra Nidoni et al 2,4 In our study it was observed that difficult cholecystectomy was noted in patients 50years of age, which is similar to the study of Lee NW et al and Kama et al 5,6 In a study conducted by Rabindra Nidoni et al in 180 cases found that Male: Female was 1:1.76.…”
Section: Resultsmentioning
confidence: 99%
“…12 In many studies, it has been stated that abdominal and epigastrium surgery might be a risk factor for conversion to open surgery. 13,14 However, there also are publications stating that it is not a risk factor. 15,16 In our study, we determined that prior abdominal surgery was not a risk factor but an adhesion makes dissection in Calot's triangle more difficult and this is a risk factor for conversion to open surgery (p < 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…Factors associated with a need for conversion are the degree of inflammation, previous upper abdominal surgery, acute cholecystitis, advanced age, male gender, dense adhesions, and obscure anatomy in Calot's triangle. 19,20 Laparoscopic ultrasound can diminish the rate of conversions without additional risk for the patient by providing exact navigation in the operating field: the decision of whether or not to convert to open surgery is based on visual monitoring of the vessels and the CBD, not on leaking bile and a hole in the portal vein or the hepatic artery. The question of protective bile duct stenting before surgery remains open; in our study it helped to delineate anatomy, and there were no conversions in the group of patients given stents prior to the LC.…”
Section: Discussionmentioning
confidence: 99%